Numerical study of premixed gas explosion in a 1-m channel partly filled with 18650 cell-like cylinders with experiments. (July 2022) - Henriksen, M.; Vaagsaether, K.; Lundberg, J.; Forseth, S.; Bjerketvedt, D.
Abstract: Abused and defective Li-ion cells can cause a catastrophic failure of a Li-ion battery (LIB), leading to severe fires and explosions. In recent years, several numerical and experimental studies have been conducted on the explosion hazard related to the vented combustible gases from failed Li-ion cells. Experimentally quantifying fundamental properties for failing LIBs is essential for understanding safety issues; however, it can be costly, time-consuming, and can be partly incomplete. Computational fluid dynamic (CFD) simulations have been an essential tool for studying the risk and consequences in the process industry. In this study, the prediction accuracy of the open-source CFD combustion model/solver XiFoam was evaluated by comparing numerical simulations and experiments of premixed gas explosions in a 1-m explosion channel partly filled with 18650 cell-like cylinders. The prediction accuracy was determined by calculating the mean geometric bias and variance for the temporal pressure evolution, maximum pressure peak, positive impulse, spatial flame front velocity for two different channel geometries, in addition to two gas compositions at several fuel-air equivalence ratios. From this method, the XiFoam model/solver gave an overall acceptable model performance for both geometries and gas composition. Highlights: Experimentally and numerically study of explosions from Li-ion battery vent gases. Explosion channel filled with 40 18650 Li-ion cell-like cylinders. Flame acceleration for two different gas compositions and two channel geometries. Evaluation of the XiFoam CFD model performance for consequence and risk analysis.